KEJADIAN BABY BLUES PADA IBU PRIMIPARA DI RSUD BANGIL PASURUAN - Restyana, Cindy Ika; Adiesti, Ferilia (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2014)
The birth and the presence are supposed to bring happiness to married couples. Most do not have adaption and psychological disorders, such as feeling sad, annoyed, tired, angry, and hopeless. The feeling that makes a reluctantly to mother to take care of their baby by the expert is called postpartum blues or commonly known as the baby blues. The purpose of this study is to determine the incidence of baby blues in primiparous mothers in RSUD Bangil Pasuruan months of 2014. Design of this study is a descriptive with case of approach the study variables are the incidence of baby blues in primiparous mothers. The population in this study are all of primiparous postpartum women 1 – 7 days in RSUD Bangil. The samples are 34 respondents taken with accidental sampling technique. The data source of this study is primary data collected with interview using instruments such as questionaires. The data are collected on May 16 to 22 2014. And are analyzed with using descriptive and the last presented in the form of a frequebcy distribution table. The result show most respondents of primiparous mother need screening again next 2 weeks later amount 21 respondents (61.8%).The most frequent symptoms that appear in women experience the baby blues almost always blame theirselves improperly when their bad condition, the mother are so sad when they cry, they sleep difficulty and sometimes like angry without proper reason. The maternal and family should really prepare their mental condition after delivery. For famililies, especially husband should always accompany their wife either before or during and after childbirth so that mothers feel comfortable and protected. The health workers should provide the delivery care to apply therapeutic communication about how to deal with labor so that the mothers and family can undergo the condition after birth.Key words : Baby Blues, Primiparous Mother